2001
DOI: 10.1046/j.1532-5415.2001.49109.x
|View full text |Cite
|
Sign up to set email alerts
|

A Nurse‐Led Interdisciplinary Intervention Program for Delirium in Elderly Hip‐Fracture Patients

Abstract: This study demonstrated the beneficial effects of an intervention program focusing on early recognition and treatment of delirium in older hip-fracture patients and confirms the reversibility of the syndrome in view of the delirium's duration and severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
340
1
14

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 325 publications
(361 citation statements)
references
References 64 publications
6
340
1
14
Order By: Relevance
“…Seven studies [18][19][20][21][22][23][24] were done in critically ill patients, 5 in geriatric general medicine patients, 9-13 3 in postoperative patients, [14][15][16] and 2 in patients who had a hip fracture. 7,8 A total of 13 of the studies were prospective investigations, [7][8][9][10][11]13,15,16,18,[21][22][23][24] and 4 were randomized control trials. [14][15][16]24 The Confusion Assessment Method or the Confusion Assessment Method for the Intensive Care Unit (CAM-ICU) was the most frequently used tool and was used in 10 studies.…”
Section: All Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven studies [18][19][20][21][22][23][24] were done in critically ill patients, 5 in geriatric general medicine patients, 9-13 3 in postoperative patients, [14][15][16] and 2 in patients who had a hip fracture. 7,8 A total of 13 of the studies were prospective investigations, [7][8][9][10][11]13,15,16,18,[21][22][23][24] and 4 were randomized control trials. [14][15][16]24 The Confusion Assessment Method or the Confusion Assessment Method for the Intensive Care Unit (CAM-ICU) was the most frequently used tool and was used in 10 studies.…”
Section: All Studiesmentioning
confidence: 99%
“…Unfortunately, most of the literature is on nonpharmacological interventions used in either general medicine, geriatric, or perioperative patients. [7][8][9][10][11][12][13][14][15][16] Although critically ill patients certainly differ from most of the populations of patients studied, one can reasonably assume that critically ill patients, who are at the highest risk for delirium, would also benefit from nonpharmacological interventions. Large randomized controlled trials with a multi-interventional approach that includes pharmacological and nonpharmacological approaches to prevent delirium are needed.…”
mentioning
confidence: 99%
“…Numerous studies have demonstrated that perioperative geriatric consultation, early surgery, effective pain management, and staff education can successfully decrease the incidence and severity of postoperative delirium in hip-fracture patients [10][11][12][13][14][15]. In the majority of these studies, many of the patients had preoperative cognitive impairment.…”
Section: Current Research On Postoperative Deliriummentioning
confidence: 99%
“…Early recognition and treatment of delirium may be the key to reduce the duration and severity of delirium and negative outcomes [10][11][12] .…”
Section: Introductionmentioning
confidence: 99%